(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
To overcome the overflow of water from the Cibeureum river in Bandung, a detailed plan is needed regarding the hydrological aspects, the environment, and the ideal capacity of the river’s cross section so that an ideal, applicative, and appropriate handling of the flood problem can be planned. This research was conducted to evaluate the flood discharge of the Cibeureum river and to plan river handling that is efficient, effective, and appropriate and able to deal with the problems of flooding caused by overflowing river water. From the results of the study, it was concluded that the Flood Discharge Plan with the Period of Return Q25 obtained a Flood Discharge of 61.62?3/sec by using the Snyder method. From the analysis of the existing river capacity compared with the flood discharge plan Q25, it is known that there is overtopping at several Cibeureum river stations / segments with a maximum height of 2 meters above the river embankment. Normalization and restoration of rivers need to be done, or returning to their original condition and function, refers to PP 38/2011 concerning rivers, especially in locations that have overtopping, among others, making new embankments, adding height of existing embankments, and river normalization (sediment dredging).